Abundance and diversity of phytoplankton at sekotong bay waters Western Lombok - Lalu Japa; Noar Muda Satyawan; Rizky Regina Kawirian (Jurnal Pijar Mipa, 2021)
Phytoplankton is one of the important components in aquatic ecosystems. This organism plays an important role as a primary producer to support the life of the tropics above it. The purposesÃÂ of this study were to reveal the abundance and diversity of phytoplankton species in the waters of Sekotong Bay, West Lombok. Sampling were conducted in July 2018 at 8 stations using plankton net and then observed at the Laboratory. The results of the abundance calculations show a varied pattern at each observation station. The highest abundance was found at station 8 (9,060 ind/L) followed by station 6 (8,300 ind/L), station 7 (6,490 ind/L), station 4 (4,440 ind/L), station 3 (3,980 ind/L) , station 5 (2,820 ind/L), station 2 (2,460 ind/L) and station 1 (2,440 ind/L). The Shannon - Wiener Species diversity Index also shows diverse patterns at each station. Station 7 has the highest diversity index value (HÃ¢â¬Â² = 3.55), followed by station 6 (HÃ¢â¬Â² = 3.46), station 8 (HÃ¢â¬Â² = 3.18), station 1 (HÃ¢â¬Â² = 2.72) , station 2 (HÃ¢â¬Â² = 2.69), station 5 (HÃ¢â¬Â² = 2.67), station 4 (HÃ¢â¬Â² = 2.33) and station 3 (HÃ¢â¬Â² = 2.26). Species dominance index at all stations at low category with the highest dominance found at station 3 (D = 0.19), followed by station 4 (D = 0.18), station 2 (D = 0.09), station 5 (D = 0, 09), station 1 (D = 0.08), station 8 (D = 0.06), station 6 (D = 0.05) and station 7 (D = 0.04). Species Evennes index (E) values ranged from 0.71 to 0.88, indicating that the number of individual species wasÃÂ relatively the same and the ecosystem was in relatively good condition. The analysis showedÃÂ that the spatial pattern of abundance and diversity of phytoplankton species in Sekotong Bay was related to the distance from the estuary.